2014
DOI: 10.1016/j.scitotenv.2014.02.126
|View full text |Cite
|
Sign up to set email alerts
|

The use of invertebrates as indicators of environmental change in alpine rivers and lakes

Abstract: 1In alpine regions climatic change will alter the balance between water sources (rainfall, ice-2 melt, snowmelt, and groundwater) for aquatic systems, particularly modifying the relative 3 contributions of meltwater, groundwater and rain to both rivers and lakes. Whilst these 4 changes are expected to have implications for alpine aquatic ecosystems, little is known about 5 potential ecological tipping points and associated indicator taxa. Within the EU-FP7 6 ACQWA project we examined changes in biotic communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 82 publications
2
41
1
Order By: Relevance
“…Still, our models illustrate the adaptation and environmental tolerance of this species group, being able to withstand harsh conditions, which we found to be their niche in alpine streams. Although we applied a different approach in contrast to other authors (Khamis et al, 2014), we congruently identified several species adapted to a high glacial influence (several Diamesa species). We are aware that the geographic scope of this study, which covered remote parts of the Eastern Alps, is relatively small compared to the geographic distribution of the chironomid species identified (e.g.…”
Section: Niche Differentiation In a Multi-species Communitysupporting
confidence: 49%
See 2 more Smart Citations
“…Still, our models illustrate the adaptation and environmental tolerance of this species group, being able to withstand harsh conditions, which we found to be their niche in alpine streams. Although we applied a different approach in contrast to other authors (Khamis et al, 2014), we congruently identified several species adapted to a high glacial influence (several Diamesa species). We are aware that the geographic scope of this study, which covered remote parts of the Eastern Alps, is relatively small compared to the geographic distribution of the chironomid species identified (e.g.…”
Section: Niche Differentiation In a Multi-species Communitysupporting
confidence: 49%
“…However, instead of comparing niche-based processes with neutral models (Vergnon et al, 2009), we provided modelled requirement-based species preferences in relation to key-environmental variables that mostly affect community structures. While other studies have used coarse indices to quantify glacial influence and selected indicator species for their changes (Khamis et al, 2014), we used reach-scale environmental variables to understand the local stressors provoking different community structures. Nevertheless, we identified similar patterns and indicator taxa.…”
Section: Niche Differentiation In a Multi-species Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…The two macro-regions are characterised by major climatic differences in water availability and temperature (López-Moreno et al, 2008), with Mediterranean climate being generally warmer, drier and comparatively of larger inter-seasonal variability than the Atlantic climate. This means potential tipping points in alpine lake ecosystems due to climate change effects (particularly through sharp changes in water temperature and dynamics; Khamis et al, 2014) is likely to happen faster across horizontal than vertical gradients in biogeographical boundary regions such as this one, with potentially unexpected effects. The changes could affect ecological processes such as niche retention in benthic biota, but they could also potentially affect longer-term biotic speciation in these regions (Doebeli and Dieckmann, 2003).…”
Section: Large Geographical Gradientsmentioning
confidence: 99%
“…For example the functional diversity of alpine stream benthic invertebrate communities can be particularly affected by climate change-driven glacier retreat (Khamis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%